Attitudes and Motivation of Afghan Students toward Learning English - Zabihullah Alimyar (Universitas Sembilanbelas November Kolaka, 2020)
AbstractThis study investigated Afghan students’ attitudes and motivation toward learning English at six different universities in Afghanistan. Several factors were believed to influence their success in learning English (i.e., motivation types as a major factor together with variables, such as gender, grades, fields of study, parental/teacher involvement, language learning anxiety and academic achievement). In searching for a reliable attitudinal profile of the subjects, quantitative research methodology was adopted along with mixed research techniques. The data was collected from 457 university students (273 male and 184 female) and 12 university EFL teachers through questionnaires and interviews. The findings showed that most of the Afghan university students held a positive attitude toward learning English and they were highly influenced by three types of motivation (i.e., instrumental, integrative, and intrinsic). Significant differences were found in the attitudes of students in terms of their fields of study, grades, and language learning anxiety. Interestingly, the findings also showed that some students were demotivated to learn EFL due to the propagation that English will no longer widely be used if NATO and US forces leave Afghanistan. It is suggested that EFL teachers should adopt motivational strategies in their classes to develop students’ positive attitudes and enhance their motivation toward learning EFL.